Violation of the rights of the companion during hospitalization for childbirth in public maternity hospitals - Lihsieh Marrero; Odaléa Maria Brüggemann; Roberta Costa; Carolina Frescura Junges; Sondre Schneck (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objective To estimate the prevalence of violation of the rights of the companion during the hospitalization of the woman for childbirth. Method Cross-sectional study conducted in public maternity hospitals in Florianopolis between 2015 and 2016, with data from individual interview with 1.145 companions. Prevalence ratio and Pearson's chi-square test were applied in the analysis. Results Women (92.8%), who received prenatal care (93.1%) and were unaware of the companions' law (92.7%) suffered more violation of rights. Not having received written guidance (93.6%), not identifying the health professional (65.0%) and not being encouraged to participate in care (55.9%) were violated rights. Welcoming and communicating with the team were the care aspects that most violated the rights of the companion. Conclusion The high prevalence of violation of rights demonstrates the disrespect and the need to value companions of choice.